2014
DOI: 10.4028/www.scientific.net/kem.599.193
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Heating of Steel Slag Asphalt Mixture

Abstract: In this research, the potential of using steel slag asphalt mixture as a self-healing material was investigated by means of microwave heating. The microwave heating rate and thermal conductivity of asphalt mixtures were tested respectively. The result shown that, the heating rate of steel slag asphalt mixtures is approximately two times faster than limestone asphalt mixtures. While its thermal conductivity is slightly lower. It is concluded that microwave heating can be used to promote self-healing of steel sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 8 publications
0
9
0
2
Order By: Relevance
“…In addition, if ferrous particles are added to the mixture, these may reflect microwave radiation and accelerate the increase of temperature [16]. In previous researches ( [17], [18]), this technique has shown potential for healing asphalt mixture A C C E P T E D M A N U S C R I P T…”
Section: Introductionmentioning
confidence: 96%
“…In addition, if ferrous particles are added to the mixture, these may reflect microwave radiation and accelerate the increase of temperature [16]. In previous researches ( [17], [18]), this technique has shown potential for healing asphalt mixture A C C E P T E D M A N U S C R I P T…”
Section: Introductionmentioning
confidence: 96%
“…They emphasized that microwave treatment had the potential to improve the bonding properties of asphalt and aggregate [ 23 ]. Sun et al studied the induced-healing performance of asphalt mixture under microwave irradiation, and proved that microwave heating induced a good heating effect for asphalt mixture containing steel slag [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…The replacement of conventional coarse aggregates (such as granite or limestone) with steel slag is another promising option [ 91 ], since its presence not only can provide better healing results but also can improve the performance of the whole mixture [ 92 ]. The research tests have identified improved load–displacement relationships with higher ductile behavior, higher heating rates with enhanced energy conversion of microwave irradiation into more thermal energy, and other improvements [ 93 , 94 , 95 ]. However, examples demonstrating that the healing performance of these mixtures with metallic wastes was slightly lower have been published too [ 96 ].…”
Section: Resultsmentioning
confidence: 99%